Anarchy, pacifism and realism: building a path to a non-violent international law. Issue 2 (4th May 2018) - Moses, Jeremy
ABSTRACT: In anarcho-pacifist thought it is argued that a consistent pacifism could only accord with anarchism, as the establishment and enforcement of any sovereign legal order necessitates the use of violence that is anathema to pacifist ethics. Yet little work has been done to think about how this relation between pacifism and anarchism might be of value in thinking about international relations and international law, where anarchical conditions are broadly recognised as prevailing. I will suggest that a more realistic proposal for promoting peace in international relations may be found in the normative propositions of Gerhart Niemeyer's Law Without Force and the 'weak pacifism' offered by Danilo Zolo, both of which depict anarchy as a condition in which a non-violent international law might be realised. The tentative argument will be advanced that perhaps it is the anarchical condition of international politics that might allow the development of a pacifist international law in the future. While such a transformation of international law cannot be instituted through a concrete programme for reform it provides a point of reference for the imagination of new forms of international justice that avoid the provision of legal/moral justifications for war.